Correlation Analysis Between Measured Rain Data with Satellite at Rainfall Station in Merapi - Ikhsan, Jazaul; Sari, Amalia Kurnia; Hairani, Ani; Hidayah, Alidina Nurul (Semesta Teknika, 2024)
Manual and automatic rain gauges often need to be revised in measuring rainfall due to various constraints. Therefore, using rain data from satellites will be a promising alternative. The rain data used is measured hourly rainfall data 20mm in 2012, 2017, and 2022. In addition, rain data from the PERSIANN and GPM satellites were also used. The analysis was carried out using the correlation coefficient (r) method, which aims to find the correlation between measured rain data and satellite rain data. The results show that the PERSIANN satellite has the highest correlation value in rain duration in two years, while the GPM satellite has the highest total depth and intensity correlation value in two years. Therefore, it can be concluded that the GPM satellite has better accuracy than the PERSIANN satellite in monitoring rain.